Toward simultaneous toughening and reinforcing of trifunctional epoxies by low loading flexible reactive triblock copolymers. Issue 31 (14th May 2018) - Tang, Bing; Kong, Miqiu; Yang, Qi; Huang, Yajiang; Li, Guangxian
Abstract : A high performance trifunctional epoxy thermoset was toughened and reinforced by a low loading of GPG with an appropriate reactive block length, which presented a homogeneous morphology. Abstract : Flexible reactive poly(glycidyl methacrylate)- b -poly(propylene glycol)- b -poly(glycidyl methacrylate) (GPG) and nonreactive poly(ethylene glycol)- b -poly(propylene glycol)- b -poly(ethylene glycol) (EPE80) were utilized to toughen a trifunctional epoxy (diglycidyl 4, 5-epoxycyclohexane-1, 2-dicarboxylate, TDE-85). In comparison with the nonreactive EPE80 and reactive GPG92 with long reactive blocks ( L reactive ), the incorporation of reactive GPG83 with short L reactive improved the comprehensive mechanical properties of the epoxy. Upon an optimal GPG83 loading of 2.5 wt%, the tensile strength, elongation at break and critical strain energy release rate ( G 1c ) increased by ca. 31%, 45.9% and 130.8%, respectively, without sacrificing the modulus and thermal stability. Morphology characterization evidenced that micro-scale domains and nanosized vesical micelles coexisted in the nonreactive EPE80 toughened systems. However, homogeneous morphologies were formed in reactive GPG83 and GPG92 toughened systems. Fracture morphology analysis suggested that GPG can toughen epoxy thermosets by incorporating flexible PPG blocks into the epoxy network, thereby enabling an energy dissipation mechanism. The good balance between the mobility of flexible PPG and degree of cross-link density leads to the simultaneous toughening and reinforcing effect of GPG83 toward the trifunctional epoxy.